Islamic Concept of Dignity of Labour and Its Effect on The Nascent Entpreneurship Model - AZEEZ, Badmus N. O. Abdul; JIMOH, Amidu Adinoyi; ACHARA, Issah Zubairu; ABDULLAHI, Abubakar Yusuf (PT. Keberlanjutan Strategis Indonesia, 2023)
Purpose: Islam is a vital force that influences economic development and business performance, and it does not impede business development, entrepreneurship, and skill acquisition. Its economic system view of entrepreneurship is an integral part of wealth creation for Muslims. The objective of this paper is to see how the concept of Islamic dignity of labor could assist Muslim participants in the area of entrepreneurship.Methodology:The methodology of this research is theoretical; hence, it applied a qualitative approach.Findings: The data collection was conducted through the personal views of experts in Islamic worldview, Islamic entrepreneurship, ethics, and understanding of al-Qur'an, Sunnah, and other Islamic sources. Undoubtedly, if the Islamic concept of dignity of labor is adhered to, it would assist the Muslims to identify the lawful and the unlawful aspects of participation in entrepreneurship. Findings showed the effect of the Islamic ethical model on the Islamic entrepreneurship design.Implication:It is therefore recommended that whatever role the Muslims want to play in entrepreneurship, the ethics inherent in the Islamic concept of dignity of labor should be applied.